Cellulose derivative-based circularly polarized light emitter and preparation method thereof
By using the structure of the left -handed thin film, fluorescent film, and right -handed hand -made thin film in the round -off launch, solve the problem of unavailable circular polarizing directions in the existing technology, and realize high -performance round polarizers Light transmitter.
Patent Information
- Application Number
- CN202411551850.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
Existing circularly polarized light emitters cannot achieve switchability in the circularly polarized direction, and there are still difficulties in controlling chirality.
The structure of the levial film, fluorescent film, and right -handed thin film with stacked slopes, the combination of the combination of the combination of the fiber cellulose nano crystal and the hydroxyvyl cellulose through the combination of the assembly of the fluorescent carbon dot and polyethylene glycol to achieve Switching of round polarization.
The direction of rounding light can be switched, and the circular polarizing light generated by the two launch modes has large asymmetric factors, which provides high -performance circular light vibration transmitters.
Smart Images

Figure CN119376004A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of circularly polarized optical materials, and in particular relates to a circularly polarized light emitter based on cellulose derivatives and a preparation method thereof. Background Art
[0002] Circularly polarized luminescence can be divided into left-handed and right-handed circularly polarized light according to the transmission direction of the light vector. At present, circularly polarized luminescent materials are widely used in 3D display, information encryption and light-induced supramolecular chirality. Studies have shown that the luminescence asymmetry factor is an important indicator of circularly polarized luminescence, and its calculation formula is: g lum =2(IL-IR) / (IL+IR), where IL and IR represent the intensities of left-handed and right-handed circularly polarized light emitted by the system, respectively. According to the above formula, g lum The value of is between +2 and -2, where +2 indicates that the system emits pure left-handed circularly polarized fluorescence, and conversely, -2 indicates that the system emits pure right-handed circularly polarized fluorescence.
[0003] At present, there are literature and patents on the preparation of circularly polarized luminescent materials by assembling chiral components with luminescent components. Related literature reports the preparation of circularly polarized luminescent systems by assembling luminescent quantum dots with chiral dopants. In related patents, cellulose nanocrystal suspension and gold nanoclusters are mixed and evaporated to induce self-assembly, resulting in a circularly polarized luminescent film based on cellulose nanocrystals.
[0004] However, controlling the chirality of circularly polarized light emission is still a difficult problem for current circularly polarized light emitters, and the circularly polarized light emitters disclosed in the above-mentioned related technologies cannot achieve switchable circular polarization direction. Summary of the invention
[0005] The purpose of the present invention is to provide a circularly polarized light emitter based on a cellulose derivative and a preparation method thereof. The circular polarization direction of the circularly polarized light emitter based on a cellulose derivative provided by the present invention is switchable. The high-performance circularly polarized light emitter with switchable chirality provided by the present invention provides a basis for the wide application of circularly polarized light emitters.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a circularly polarized light emitter based on cellulose derivatives, comprising a left-handed chiral film, a fluorescent film and a right-handed chiral film which are sequentially stacked; the left-handed chiral film is a left-handed chiral film based on chiral nematic cellulose nanocrystals, and the right-handed chiral film is a right-handed chiral film based on chiral nematic hydroxypropyl cellulose.
[0008] Preferably, the fluorescent film is a polyvinyl alcohol-based fluorescent film; the polyvinyl alcohol-based fluorescent film is obtained by film-forming fluorescent carbon dots and polyvinyl alcohol.
[0009] The present invention provides a method for preparing a circularly polarized light emitter based on a cellulose derivative as described in the above technical solution, comprising the following steps:
[0010] The chiral nematic cellulose nanocrystal suspension and glucose are mixed to form a membrane, thereby obtaining a left-handed chiral film based on the chiral nematic cellulose nanocrystal;
[0011] The chiral nematic hydroxypropyl cellulose precursor is made into a film to obtain a right-handed chiral film based on the chiral nematic hydroxypropyl cellulose;
[0012] The left-handed chiral film, the fluorescent film and the right-handed chiral film are stacked in sequence and then fixed with an ultraviolet curing agent to obtain the circularly polarized light emitter based on the cellulose derivative.
[0013] Preferably, the method for preparing the chiral nematic cellulose nanocrystal suspension comprises the following steps:
[0014] The cellulose and sulfuric acid are mixed for hydrolysis reaction to obtain the chiral nematic cellulose nanocrystal suspension; the mass concentration of the sulfuric acid is 60-80%, and the usage ratio of the cellulose and the sulfuric acid is (15-35) g: (150-350) mL.
[0015] Preferably, the mass percentage of the chiral nematic cellulose nanocrystal suspension is 1 to 5%;
[0016] The mass ratio of the chiral nematic cellulose nanocrystal suspension to the glucose is (3-4): (0.01-0.1).
[0017] Preferably, the method for preparing the chiral nematic hydroxypropyl cellulose precursor comprises the following steps:
[0018] Hydroxypropyl cellulose, hydroxyethyl methacrylate and water are mixed to obtain the chiral nematic hydroxypropyl cellulose precursor.
[0019] Preferably, the mass ratio of the hydroxypropyl cellulose to the hydroxyethyl methacrylate is (4-8): (0.5-1);
[0020] The dosage ratio of the hydroxypropyl cellulose and water is (4-8) g: (15-20) mL.
[0021] Preferably, the chiral nematic hydroxypropyl cellulose precursor is formed by drying the film, and the drying temperature is 50-90°C.
[0022] Preferably, the method for preparing the fluorescent film comprises the following steps:
[0023] The carbon dot solution is mixed with polyvinyl alcohol to obtain a mixed solution; the mixed solution is used to form a film to obtain a polyvinyl alcohol-based fluorescent film; the carbon dot solution is a carbon dot solution using citric acid as a carbon source and polyethyleneimine for surface modification.
[0024] Preferably, the mass concentration of the carbon dot solution is 1-5 mg / mL; the mass ratio of the carbon dot solution to polyvinyl alcohol is (1-3):(0.1-0.3).
[0025] The present invention provides a circularly polarized light emitter based on cellulose derivatives, comprising a left-handed chiral film, a fluorescent film and a right-handed chiral film which are sequentially stacked; the left-handed chiral film is a left-handed chiral film based on chiral nematic cellulose nanocrystals, and the right-handed chiral film is a right-handed chiral film based on chiral nematic hydroxypropyl cellulose. The chiral nematic cellulose derivative substrate of the circularly polarized light emitter based on chiral nematic cellulose derivatives provided by the present invention comprises a left-handed chiral film based on chiral nematic cellulose nanocrystals and a right-handed chiral film based on chiral nematic hydroxypropyl cellulose, and a fluorescent film is arranged between the left-handed chiral film and the right-handed chiral film. The circularly polarized light emitter provided by the present invention not only has a large asymmetry factor, but also has the characteristic of switchable circular polarization direction.
[0026] The present invention provides a preparation method of a circularly polarized light emitter based on cellulose derivatives as described in the above technical solution, comprising the following steps: mixing a chiral nematic cellulose nanocrystal suspension with glucose to form a film, thereby obtaining a left-handed chiral film based on chiral nematic cellulose nanocrystals; forming a film of a chiral nematic hydroxypropyl cellulose precursor to obtain a right-handed chiral film based on chiral nematic hydroxypropyl cellulose; sequentially superimposing the left-handed chiral film, a fluorescent film and the right-handed chiral film, and then fixing them with an ultraviolet curing agent to obtain the circularly polarized light emitter based on cellulose derivatives. The preparation method provided by the present invention has easy-to-obtain raw materials, simple steps, is green and environmentally friendly, and is suitable for industrialized expansion of production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a photo of the circularly polarized light emitter provided in Example 1 of the present invention;
[0028] Figure 2 A circularly polarized light spectrum diagram of the circularly polarized light transmitter provided in Example 1 of the present invention;
[0029] Figure 3 A distribution diagram of the circularly polarized light asymmetry factor of the circularly polarized light transmitter provided in Example 1 of the present invention;
[0030] Figure 4 This is a distribution diagram of the asymmetry factor of the circularly polarized light emitter provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention provides a circularly polarized light emitter based on cellulose derivatives, comprising a left-handed chiral film, a fluorescent film and a right-handed chiral film which are sequentially stacked; the left-handed chiral film is a left-handed chiral film based on chiral nematic cellulose nanocrystals, and the right-handed chiral film is a right-handed chiral film based on chiral nematic hydroxypropyl cellulose.
[0032] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0033] The circularly polarized light emitter based on cellulose derivatives provided by the present invention comprises a left-handed chiral film. In the present invention, the left-handed chiral film is a left-handed chiral film based on chiral nematic cellulose nanocrystals. The left-handed chiral film based on chiral nematic cellulose nanocrystals is preferably obtained by film-forming a chiral nematic cellulose nanocrystal suspension and glucose.
[0034] The circularly polarized light emitter based on cellulose derivatives provided by the present invention comprises a fluorescent film arranged on the surface of the left-handed chiral film. In the present invention, the fluorescent film is preferably a fluorescent film based on polyvinyl alcohol. The fluorescent film based on polyvinyl alcohol is preferably obtained by film-forming fluorescent carbon dots and polyvinyl alcohol.
[0035] The circularly polarized light emitter based on cellulose derivatives provided by the present invention comprises a right-handed chiral film arranged on the surface of the fluorescent film. In the present invention, the right-handed chiral film is a right-handed chiral film based on chiral nematic hydroxypropyl cellulose. The right-handed chiral film based on chiral nematic hydroxypropyl cellulose is preferably obtained by film-making from a chiral nematic hydroxypropyl cellulose precursor. The chiral nematic hydroxypropyl cellulose precursor preferably comprises hydroxypropyl cellulose, hydroxyethyl methacrylate and water.
[0036] In the present invention, the left-handed chiral film, the fluorescent film and the right-handed chiral film stacked in sequence are preferably fixed by an ultraviolet curing agent.
[0037] The present invention provides a method for preparing a circularly polarized light emitter based on a cellulose derivative as described in the above technical solution, comprising the following steps:
[0038] The chiral nematic cellulose nanocrystal suspension and glucose are mixed to form a membrane, thereby obtaining a left-handed chiral film based on the chiral nematic cellulose nanocrystal;
[0039] The chiral nematic hydroxypropyl cellulose precursor is made into a film to obtain a right-handed chiral film based on the chiral nematic hydroxypropyl cellulose;
[0040] The left-handed chiral film, the fluorescent film and the right-handed chiral film are stacked in sequence and then fixed with an ultraviolet curing agent to obtain the circularly polarized light emitter based on the cellulose derivative.
[0041] The present invention mixes a chiral nematic cellulose nanocrystal suspension with glucose to form a film, thereby obtaining a left-handed chiral film based on chiral nematic cellulose nanocrystals. In the present invention, the preparation method of the chiral nematic cellulose nanocrystal suspension preferably comprises the following steps: mixing cellulose and sulfuric acid for hydrolysis reaction to obtain the chiral nematic cellulose nanocrystal suspension. The cellulose is preferably pulp cellulose. The mass concentration of the sulfuric acid is preferably 50-80%, more preferably 60-70%, most preferably 62-65%, and 64% in the embodiment. The amount ratio of the cellulose to the sulfuric acid is preferably (15-35) g: (150-350) mL, more preferably (20-30) g: (200-300) mL. The hydrolysis reaction is preferably carried out under stirring, and the stirring speed of the hydrolysis reaction is preferably 400-600 rpm, and specifically 500 rpm in the embodiment. The temperature of the hydrolysis reaction is preferably 30-50° C., and specifically 45° C. in the embodiment, and the time of the hydrolysis reaction is preferably 1-2 h. The hydrolysis reaction is preferably carried out under the condition of heating in a water bath. In the present invention, after the hydrolysis reaction is completed, a hydrolysis reaction liquid is directly obtained. The present invention preferably dialyzes and concentrates the hydrolysis reaction liquid in sequence to obtain the chiral nematic cellulose nanocrystal suspension. The present invention has no special requirements for the specific implementation of the dialysis. The concentration is preferably carried out in an oven, and the concentration temperature is preferably 70 to 80°C. The mass percentage of the chiral nematic cellulose nanocrystal suspension is preferably 1 to 5%, more preferably 2 to 4%, and most preferably 3 to 4%.
[0042] After obtaining the chiral nematic cellulose nanocrystal suspension, the present invention mixes the chiral nematic cellulose nanocrystal suspension with glucose to form a film. The mass ratio of the chiral nematic cellulose nanocrystal suspension to the glucose is preferably (3-4): (0.01-0.1). The mixing time is preferably 1-2 hours. In the present invention, the film formation is preferably carried out by drying. In the present invention, the drying temperature is preferably room temperature, and no additional heating and cooling are required; the present invention has no special requirements for the drying environment, and the drying can be carried out in the air state; the present invention has no specific requirements for the drying time, and the solvent can be completely removed. In a specific embodiment of the present invention, the film formation preferably specifically includes the following steps: pouring the mixture obtained by mixing the chiral nematic cellulose nanocrystal suspension and glucose into a polystyrene box for drying. The present invention has no special requirements for the size and area of the polystyrene box, which is specifically determined according to the required film area and thickness. The present invention dries the mixture under air room temperature to naturally evaporate the solvent in the mixture, thereby retaining the chiral nematic structure of the cellulose nanocrystal to the greatest extent, and finally obtaining a left-handed chiral film based on chiral nematic cellulose nanocrystals.
[0043] The present invention forms a film of a chiral nematic hydroxypropyl cellulose precursor to obtain a right-handed chiral film based on the chiral nematic hydroxypropyl cellulose. In the present invention, the preparation method of the chiral nematic hydroxypropyl cellulose precursor preferably includes the following steps: mixing hydroxypropyl cellulose (HPC), hydroxyethyl methacrylate and water to obtain the chiral nematic hydroxypropyl cellulose precursor. The water is preferably deionized water. The mass ratio of the hydroxypropyl cellulose and the hydroxyethyl methacrylate is preferably (4-8): (0.5-1), and specifically 6.5:0.6 in the embodiment. The dosage ratio of the hydroxypropyl cellulose and water is preferably (4-8) g: (15-20) mL, and specifically 6.5 g: 16 mL in the embodiment. In the present invention, the mixing of the hydroxypropyl cellulose, hydroxyethyl methacrylate and water preferably includes: mixing the hydroxyethyl methacrylate with water, then adding the HPC, and finally performing ultrasonic treatment and centrifugation treatment in sequence. The ultrasonic treatment time is preferably 20 to 40 minutes, and the purpose of the ultrasonic treatment is to evenly disperse hydroxypropyl cellulose, hydroxyethyl methacrylate and water. The rotation speed of the centrifugal treatment is preferably 8000 to 10000 r / min, and the centrifugal treatment time is preferably 10 to 20 minutes.
[0044] In the present invention, the method for forming a film of the chiral nematic hydroxypropyl cellulose precursor is preferably drying film, and the temperature of the drying film is preferably 50-90°C. In a specific embodiment of the present invention, the film formation preferably includes: pouring the chiral nematic hydroxypropyl cellulose precursor into a polystyrene box for drying. The present invention has no special requirements for the size and area of the polystyrene box, which is specifically determined according to the required film area and thickness. In the present invention, the drying temperature is preferably 50-90°C, more preferably 60-85°C, and most preferably 60-80°C. The present invention has no specific requirements for the drying time, as long as the solvent can be completely removed. After drying, a right-handed chiral film based on chiral nematic hydroxypropyl cellulose is obtained.
[0045] After obtaining a left-handed chiral film based on chiral nematic cellulose nanocrystals and a right-handed chiral film based on chiral nematic hydroxypropyl cellulose, the present invention sequentially stacks the left-handed chiral film, the fluorescent film and the right-handed chiral film, and then fixes them with an ultraviolet curing agent to obtain the circularly polarized light emitter based on the cellulose derivative.
[0046] In the present invention, the method for preparing the fluorescent film preferably comprises the following steps: mixing a carbon dot solution with polyvinyl alcohol to obtain a mixed solution; and forming a film from the mixed solution to obtain a polyvinyl alcohol-based fluorescent film. In the present invention, the carbon dot solution is preferably a carbon dot solution using citric acid as a carbon source and polyethylene imine for surface modification. In the present invention, the method for preparing the carbon dot solution preferably comprises: mixing citric acid, polyethylene imine and water and then performing a hydrothermal reaction to obtain the carbon dot solution. The mass ratio of citric acid, polyethylene imine and water is preferably (0.1-0.3):(0.6-0.8):(15-20). The temperature of the hydrothermal reaction is preferably 150-220°C, and the time of the hydrothermal reaction is preferably 8-10h. The mass concentration of the carbon dot solution is preferably 1-5 mg / mL, more preferably 2-4 mg / mL. The mass concentration of the carbon dot solution is the mass concentration of carbon quantum dots in the carbon dot solution. The mass ratio of the carbon dot solution and polyvinyl alcohol is preferably (1-3):(0.1-0.3).
[0047] In the present invention, the raw materials for preparing the fluorescent film preferably also include water, and the mixture of the carbon dot solution and polyvinyl alcohol is preferably adaptively replaced by a mixture of carbon dot solution, polyvinyl alcohol and water. The mass of the carbon dot solution, polyvinyl alcohol and water is preferably (1-3): (0.1-0.3): (3-5), and specifically 1: 0.15: 3 in the embodiment. After obtaining the mixed solution, the present invention forms a film with the mixed solution to obtain a fluorescent film based on polyvinyl alcohol. In the present invention, the method for forming a film with the mixed solution is preferably drying film formation, and the specific implementation method of the drying film formation is preferably: pouring the mixed solution into a polystyrene box for drying, and the present invention has no special requirements for the size and area of the polystyrene box; in the present invention, the drying temperature is preferably room temperature, and no additional heating and cooling are required; the present invention has no special requirements for the drying environment, and it can be dried in the air state; the present invention has no specific requirements for the drying time, and it can be completely removed to finally obtain a fluorescent film.
[0048] After obtaining chiral nematic cellulose nanocrystals, left-handed chiral films, and right-handed chiral films and fluorescent films based on chiral nematic hydroxypropyl cellulose, the present invention sequentially stacks the left-handed chiral films, fluorescent films, and right-handed chiral films, and then fixes them with an ultraviolet curing agent to obtain the circularly polarized light emitter based on cellulose derivatives. In a specific embodiment of the present invention, the present invention preferably sequentially stacks the left-handed chiral films, fluorescent films, and right-handed chiral films, and then clamps them with a quartz plate, and finally fixes them with an ultraviolet curing agent. In the present invention, there is no special requirement for the size of the quartz plate: In the present invention, there is no requirement for the curing time of the ultraviolet curing agent, and it is sufficient to cure until it is completely cured, and finally a circularly polarized light emitter based on cellulose derivatives is obtained.
[0049] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] The preparation method of the carbon dot solution in the following examples specifically includes:
[0051] Citric acid, polyethyleneimine and water were mixed in a mass ratio of 0.1:0.6:15 to obtain a mixed solution; the mixed solution was subjected to a hydrothermal reaction at a temperature of 220° C. for 10 h to obtain a carbon dot solution having a mass concentration of 2 mg / mL.
[0052] Example 1
[0053] Weigh 15 g of pulp cellulose and add it into a round-bottom flask, add 150 mL of 64% sulfuric acid (H2SO4), control the stirring speed to 500 rpm, stir in a 45°C water bath for 1 hour to obtain a hydrolysis reaction liquid, dialyze the obtained hydrolysis reaction liquid, and then concentrate the dialyzed suspension in an oven (80°C) to a mass concentration of 3% to obtain a chiral nematic cellulose nanocrystal suspension.
[0054] 0.01 g of glucose was added to a 3 wt% cellulose nanocrystal suspension (4.0 g) and mixed for 2 hours. The mixed solution was placed in a polystyrene box and evaporated at room temperature for 2 to 3 days to obtain a left-handed chiral film based on chiral nematic cellulose nanocrystals.
[0055] Hydroxyethyl methacrylate (0.6 g) was mixed in 16 g of deionized water. Then, 6.5 g of HPC was dispersed in the above solution. The resulting solution was ultrasonically treated for 30 min to ensure complete dissolution, and a uniform hydroxypropyl fiber precursor was prepared by centrifugation at 10000 r / min for 10 min. The prepared precursor was poured into a polystyrene square box. Then, the solution was scraped off with a glass plate. After standing for 10 min, the sample was dried at 80 ° C to obtain a right-handed chiral membrane based on chiral nematic hydroxypropyl cellulose.
[0056] 1.0 g of carbon dot solution (2 mg / mL) and 0.15 g of polyvinyl alcohol were added to 3.0 g of water, followed by vigorous stirring to obtain a uniform composite suspension, which was then cast into a polystyrene box and dried at ambient temperature to obtain a fluorescent film.
[0057] The left-handed chiral film, fluorescent film and right-handed chiral film prepared in this example are stacked together in sequence. Then, they are clamped together with two quartz plates. In addition, a UV curable adhesive is applied around the quartz plates. Finally, the two glass plates are irradiated with an ultraviolet lamp to cure the UV curable adhesive, thereby obtaining a circularly polarized light emitter based on a chiral nematic cellulose derivative.
[0058] The luminescence of the circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this example was detected, and the results obtained are as follows: Figure 1 shown; according to Figure 1 It can be seen that the circularly polarized light emitter prepared in this embodiment generates bright blue fluorescence after being excited by ultraviolet light.
[0059] The circular polarization spectrum of the circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this embodiment was tested, and the results were as follows: Figure 2 shown; according to Figure 2It can be seen that the circularly polarized fluorescence spectrum has two peaks in opposite directions near 430 nm, indicating that the circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this example has switchable circularly polarized emission characteristics.
[0060] Asymmetry factor g of circularly polarized spectra of circularly polarized light emitters based on chiral nematic cellulose derivatives lum The test results are as follows Figure 3 shown; according to Figure 3 It can be seen that the circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this embodiment has two asymmetric factors g near 430nm: lum , which corresponds to the spectrum of circularly polarized fluorescence spectrum.
[0061] Example 2
[0062] Weigh 35 g of pulp cellulose into a round-bottom flask, add 300 mL of 64% sulfuric acid (H2SO4), control the stirring speed to 500 rpm, stir in a 45°C water bath for 1 hour to obtain a hydrolysis reaction liquid, dialyze the obtained hydrolysis reaction liquid, and then concentrate the dialyzed suspension in an oven (80°C) to a mass concentration of 3% to obtain a chiral nematic cellulose nanocrystal suspension.
[0063] 0.02 g of glucose was added to a 3 wt% cellulose nanocrystal suspension (4.0 g) and mixed for 2 hours. The mixed solution was placed in a polystyrene box and evaporated at room temperature for 2 to 3 days to obtain a left-handed chiral film based on chiral nematic cellulose nanocrystals.
[0064] Hydroxyethyl methacrylate (0.8 g) was mixed in 18 g of deionized water. Then, 6.5 g of HPC was dispersed in the above solution. The resulting solution was ultrasonically treated for 30 min to ensure complete dissolution, and a uniform hydroxypropyl fiber precursor was prepared by centrifugation at 10000 r / min for 10 min. The prepared precursor was poured into a polystyrene square box. Then, the solution was scraped off with a glass plate. After standing for 10 min, the sample was dried at 70 ° C to obtain a right-handed chiral membrane based on chiral nematic hydroxypropyl cellulose.
[0065] 1.5 g of carbon dot solution (2 mg / mL) and 0.2 g of polyvinyl alcohol were added to 3.0 g of water, followed by vigorous stirring to obtain a uniform composite suspension, which was then cast into a polystyrene box and dried at ambient temperature to obtain a fluorescent film.
[0066] The left-handed chiral film, fluorescent film and right-handed chiral film prepared in this example are stacked together in sequence. Then, they are clamped together with two quartz plates. In addition, a UV curable adhesive is applied around the quartz plates. Finally, the two glass plates are irradiated with an ultraviolet lamp to cure the UV curable adhesive, thereby obtaining a circularly polarized light emitter based on a chiral nematic cellulose derivative.
[0067] The circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this example was tested in the manner of Example 1. The results showed that it also had two circularly polarized emission characteristics and corresponding asymmetric factors, which were basically consistent with the results of Example 1.
[0068] Example 3
[0069] Weigh 20 g of pulp cellulose and add it into a round-bottom flask, add 200 mL of 64% sulfuric acid (H2SO4), control the stirring speed to 500 rpm, stir in a 45°C water bath for 1 hour to obtain a hydrolysis reaction liquid, dialyze the obtained hydrolysis reaction liquid, and then concentrate the dialyzed suspension in an oven (80°C) to a mass concentration of 3% to obtain a chiral nematic cellulose nanocrystal suspension.
[0070] 0.03 g of glucose was added to a 3 wt% cellulose nanocrystal suspension (9.0 g) and mixed for 2 hours. The mixed solution was placed in a polystyrene box and evaporated at room temperature for 2 to 3 days to obtain a left-handed chiral film based on chiral nematic cellulose nanocrystals.
[0071] Hydroxyethyl methacrylate (1.0 g) was mixed in 20 g of deionized water. Then, 6.5 g of HPC was dispersed in the above solution. The resulting solution was ultrasonically treated for 30 min to ensure complete dissolution, and a uniform hydroxypropyl fiber precursor was prepared by centrifugation at 10000 r / min for 10 min. The prepared precursor was poured into a polystyrene square box. Then, the solution was scraped off with a glass plate. After standing for 10 min, the sample was dried at 60 ° C to obtain a right-handed chiral membrane based on chiral nematic hydroxypropyl cellulose.
[0072] 2.0 g of carbon dot solution (2 mg / mL) and 0.25 g of polyvinyl alcohol were added to 5.0 g of water, followed by vigorous stirring to obtain a uniform composite suspension, which was then cast into a polystyrene box and dried at ambient temperature to obtain a fluorescent film.
[0073] The left-handed chiral film, fluorescent film and right-handed chiral film prepared in this example are stacked together in sequence. Then, they are clamped together with two quartz plates. In addition, a UV curable adhesive is applied around the quartz plates. Finally, the two glass plates are irradiated with an ultraviolet lamp to cure the UV curable adhesive, thereby obtaining a circularly polarized light emitter based on a chiral nematic cellulose derivative.
[0074] The circularly polarized light emitter based on the chiral nematic cellulose derivative prepared in this example was tested in the manner of Example 1. The results showed that it also had two circularly polarized emission characteristics and corresponding asymmetric factors, which were basically consistent with the results of Example 1.
[0075] As can be seen from the above embodiments, the present invention provides a method for preparing a circularly polarized light emitter based on a chiral nematic cellulose derivative, comprising the following steps: mixing cellulose and sulfuric acid for hydrolysis reaction to obtain a cellulose nanocrystal suspension, and then mixing with glucose to form a film to obtain a left-handed chiral film based on chiral nematic cellulose nanocrystals; mixing hydroxypropyl cellulose and hydroxyethyl methacrylate with water to obtain a chiral nematic hydroxypropyl cellulose precursor, and after drying, obtaining a right-handed chiral film based on chiral nematic hydroxypropyl cellulose. Mixing fluorescent carbon dots with polyvinyl alcohol, and drying to obtain a fluorescent film based on polyvinyl alcohol. The left-handed chiral film, the fluorescent film, and the right-handed chiral film are sequentially stacked together, clamped with a quartz sheet, and fixed with an ultraviolet curing agent to obtain a circularly polarized light emitter based on a cellulose derivative. The raw materials are easily available, the steps are simple, and it is green and environmentally friendly.
[0076] The results of the embodiments show that the circularly polarized light emitter provided by the present invention can not only switch the circular polarization direction by switching the light emission mode, but also the circularly polarized lights generated by the two emission modes have a large asymmetry factor.
[0077] Comparative Example 1
[0078] Weigh 15 g of pulp cellulose and add it into a round-bottom flask, add 150 mL of 64% sulfuric acid (H2SO4), control the stirring speed to 500 rpm, stir in a 45°C water bath for 1 hour to obtain a hydrolysis reaction liquid, dialyze the obtained hydrolysis reaction liquid, and then concentrate the dialyzed suspension in an oven (80°C) to a mass concentration of 3% to obtain a chiral nematic cellulose nanocrystal suspension.
[0079] 0.01 g of glucose was added to a 3 wt% cellulose nanocrystal suspension (4.0 g) and mixed for 2 hours. The mixed solution was placed in a polystyrene box and evaporated at room temperature for 2 to 3 days to obtain a left-handed chiral film based on chiral nematic cellulose nanocrystals.
[0080] Hydroxyethyl methacrylate (0.6 g) was mixed in 16 g of deionized water. Then, 6.5 g of HPC was dispersed in the above solution. The resulting solution was ultrasonically treated for 30 min to ensure complete dissolution, and a uniform hydroxypropyl fiber precursor was prepared by centrifugation at 10000 r / min for 10 min. The prepared precursor was poured into a polystyrene square box. Then, the solution was scraped off with a glass plate. After standing for 10 min, the sample was dried at 80 ° C to obtain a right-handed chiral film based on chiral nematic hydroxypropyl cellulose.
[0081] The left-handed chiral film and the right-handed chiral film are stacked together in sequence. Then, they are clamped together with two quartz plates. In addition, a UV curable adhesive is applied around the quartz plates. Finally, the two glass plates are irradiated with an ultraviolet lamp to cure the UV curable adhesive, thereby obtaining a circularly polarized light emitter.
[0082] The circularly polarized light emitter prepared in Comparative Example 1 only combines two cellulose derivative films together, and cannot achieve the effect of switching the chirality of circularly polarized light. Figure 4 As shown, when the transmitter is in Mode 1 (Mode 1), right-handed circularly polarized light is generated, while when it is in Mode 2 (Mode 2), left-handed circularly polarized light cannot be generated.
[0083] Therefore, the circularly polarized light emitter based on cellulose derivatives provided by the present invention adopts the structural characteristics of a left-handed chiral film, a fluorescent film and a right-handed chiral film stacked in sequence, and the fluorescent film is introduced between the left-handed chiral film and the right-handed chiral film as the light-emitting layer to obtain an emitter, thereby achieving a switching effect of circularly polarized light.
[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A circularly polarized light emitter based on cellulose derivatives, characterized in that: The invention comprises a left-handed chiral film, a fluorescent film and a right-handed chiral film which are stacked in sequence; the left-handed chiral film is a left-handed chiral film based on chiral nematic cellulose nanocrystals, and the right-handed chiral film is a right-handed chiral film based on chiral nematic hydroxypropyl cellulose.
2. The circularly polarized light emitter based on cellulose derivatives according to claim 1, characterized in that: The fluorescent film is a polyvinyl alcohol-based fluorescent film; the polyvinyl alcohol-based fluorescent film is obtained by film-forming fluorescent carbon dots and polyvinyl alcohol.
3. The method for preparing a circularly polarized light emitter based on a cellulose derivative according to claim 1 or 2, characterized in that: The following steps are involved: The chiral nematic cellulose nanocrystal suspension and glucose are mixed to form a membrane, thereby obtaining a left-handed chiral film based on the chiral nematic cellulose nanocrystal; The chiral nematic hydroxypropyl cellulose precursor is made into a film to obtain a right-handed chiral film based on the chiral nematic hydroxypropyl cellulose; The left-handed chiral film, the fluorescent film and the right-handed chiral film are stacked in sequence and then fixed with an ultraviolet curing agent to obtain the circularly polarized light emitter based on the cellulose derivative.
4. The preparation method according to claim 3, characterized in that: The preparation method of the chiral nematic cellulose nanocrystal suspension comprises the following steps: The cellulose and sulfuric acid are mixed for hydrolysis reaction to obtain the chiral nematic cellulose nanocrystal suspension; the mass concentration of the sulfuric acid is 60-80%, and the usage ratio of the cellulose and the sulfuric acid is (15-35) g: (150-350) mL.
5. The preparation method according to claim 3 or 4, characterized in that: The mass percentage of the chiral nematic cellulose nanocrystal suspension is 1 to 5%; The mass ratio of the chiral nematic cellulose nanocrystal suspension to the glucose is (3-4): (0.01-0.1).
6. The preparation method according to claim 3, characterized in that: The preparation method of the chiral nematic hydroxypropyl cellulose precursor comprises the following steps: Hydroxypropyl cellulose, hydroxyethyl methacrylate and water are mixed to obtain the chiral nematic hydroxypropyl cellulose precursor.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the hydroxypropyl cellulose to the hydroxyethyl methacrylate is (4-8): (0.5-1); The dosage ratio of the hydroxypropyl cellulose and water is (4-8) g: (15-20) mL.
8. The preparation method according to claim 3, 6 or 7, characterized in that: The chiral nematic hydroxypropyl cellulose precursor is prepared by drying the film, and the drying film forming temperature is 50-90°C.
9. The preparation method according to claim 3, characterized in that: The method for preparing the fluorescent film comprises the following steps: The carbon dot solution is mixed with polyvinyl alcohol to obtain a mixed solution; the mixed solution is used to form a film to obtain a polyvinyl alcohol-based fluorescent film; the carbon dot solution is a carbon dot solution using citric acid as a carbon source and polyethyleneimine for surface modification.
10. The preparation method according to claim 9, characterized in that: The mass concentration of the carbon dot solution is 1-5 mg / mL; the mass ratio of the carbon dot solution to polyvinyl alcohol is (1-3):(0.1-0.3).